Optimization of Spray Drying Parameters for Passion Fruit Juice Powder: Physicochemical and Quality Evaluation - K.S. Fathima; P. Fathima Rinshana; G.K. Rajesh; N.P. Shamna; K.K. Ajeeshkumar (Archives of Current Research International, 2025)
Passion fruit is rich in juice and valued for its pleasant flavour, aroma, and nutritional profile, but its high perishability limits direct utilization. In this study, spray drying was employed to convert yellow passion fruit juice into a stable powder using a maltodextrin–corn starch (3:2) carrier system. Seventeen experimental trials were conducted to evaluate the effects of wall material concentration (15%, 17.5%, and 20% w/v), inlet air temperature (150°C, 160°C, and 170°C) and feed pump speed (8, 10, and 12 rpm) on quality parameters of spray dried powder. The effects of wall material concentration, inlet air temperature, and feed pump speed were evaluated using a Box–Behnken response surface methodology design. The process was optimized at 12% maltodextrin, 8% corn starch, 165 °C inlet temperature, and 12 rpm feed pump speed, resulting in a powder yield of 61.23% with low moisture content (1.62%), excellent dispersibility (89.32%), and rapid wettability (12.42 s). The optimized powder also retained desirable colour characteristics (ΔE = 20.37), ensuring good reconstitution properties. These findings demonstrate that optimized spray drying can significantly improve the shelf stability and functional quality of passion fruit juice powder, supporting its application in the food and nutraceutical industry.